Nontoxic KBBF Family Member Zn(2)BO(3)(OH): Balance between Beneficial Layered Structure and Layer Tendency - Wang, Xuefei (Adv Sci (Weinh), 2019)
The conflict between beneficial layered structure for performances and layered growth habits in KBe(2)BO(3)F(2) (KBBF) always restricts its practical applications. A beryllium‐free KBBF family member, Zn(2)BO(3)(OH), is explored to feature the same topological layer with KBBF by replacing [BeO(3)F](5−) with [ZnO(3)(OH)](5−) and excellent UV performances. It exhibits a second harmonic generation response of about 1.5 × KH(2)PO(4) with the UV cutoff edge of 204 nm. The birefringence of Zn(2)BO(3)(OH) in the visible region is about 0.067, which is larger than those of commercial UV crystals LiB(3)O(5), CsB(3)O(5), and CsLiB(6)O(10). Additionally, it has excellent thermal and water‐resistant stabilities. Owing to the removal of interlayer cations, Zn(2)BO(3)(OH) shows better growth habits than KBBF while achieving the balance between beneficial layered structure and layer tendency.